Geoffrey Chaucer - Wallace, David
Includes bibliographical references and index.; Cover; Geoffrey Chaucer: A New Introduction; Copyright; Dedication; Contents; Acknowledgements; List of Illustrations; Lis t of Abbreviations; 1: Beginnings; Designing Poetry; Persona; `Chaucer was a Class Traitor; European Theatres; Theatres of `War! War!; 2: Schoolrooms, Science, Female Intuition; Female Learning, Womens Intuition; 3: A Life in Poetry; French Lessons; Italian Poetry and `Drasty English Rhyming; Italian Liberation, Rhyme Royal, and the Path to Troilus and Criseyde; 4: Poetry at Last: Troilus and Criseyde; 5: Organizing, Disorganizing: The Canterbury Tales